Comparison of Survival Between Primary Debulking Surgery Versus Neoadjuvant Chemotherapy for Ovarian Cancers in a Personalized Treatment Cohort - Feng, Zheng; Wen, Hao; Li, Ruimin; Liu, Shuai; Fu, Yi; Chen, Xiaojun; Bi, Rui; Ju, Xingzhu; Wu, Xiaohua (Frontiers in Oncology, 2021)
Objective To compare survival between primary debulking surgery (PDS) and neoadjuvant chemotherapy (NACT) for the treatment of ovarian cancer patients per our selective protocol. Methods Between Sep 1st, 2015, and Aug 31st, 2017, 161 patients were enrolled in our prospective cohort. All of the patients received preoperative clinic-radiological assessments, according to the Suidan criteria for R0 resection. Patients with a score of 0–2 received PDS. Patients with a score of ≥3 were counseled on the choices of PDS, NACT, or an optional staging laparoscopy, according to the Fagotti criteria. Clinic-pathological data were prospectively collected until May 1st, 2020, and the impacts of different treatment strategies on progression-free survival (PFS) and overall survival (OS) were analyzed. Results 110 patients underwent PDS, and 51 patients received NACT with consequent interval debulking surgery. The R0 resection rate was 57.8%. All but one of the patients received platinum-based chemotherapy, and 105 (65.2%) patients were platinum-sensitive. Based on the univariate analysis, the PDS group exhibited prolonged PFS compared with the NACT group (P=0.029). The subgroup analysis showed that patients receiving NACT with residual disease (RD) exhibited the worst PFS (P=0.001). Based on the multivariate analysis, NACT with RD was still an independent impaired factor for PFS (P=0.04). However, NACT did not affect OS in the univariate or multivariate analyses. Conclusion In our prospective cohort, NACT ovarian patients exhibited inferior PFS and noninferior OS compared with PDS patients. Given our selective protocol, NACT cannot be arbitrarily denied while appropriate PDS is still a priority.